Synergistic therapy for orthotopic gliomas via biomimetic nanosonosensitizer-mediated sonodynamic therapy and ferroptosis. (14th June 2022) - Zhu, Mingting; Wu, Pengying; Li, Yan; Zhang, Lei; Zong, Yujin; Wan, Mingxi
Abstract : The design of a biomimetic sonosensitizer, opening the blood–brain barrier by focused ultrasound and synergistic therapy via noninvasive sonodynamic therapy and ferroptosis. Abstract : Ferroptosis is an emerging form of programmed cell death, and its combination with sonodynamic therapy (SDT) for anti-tumor activity is gradually attracting attention. However, their application against gliomas has not been studied. Herein, multifunctional cancer homologous targeting biomimetic nanoparticles (PIOC@CM NPs) encapsulating both Fe3 O4 and Ce6 were constructed as a nanosonosensitizer. Based on focused ultrasound (US) combined with circulating microbubbles (MBs) to open the blood–brain barrier (BBB) in a safe and transient manner, the development of a therapeutic strategy to integrate the biomimetic nanosonosensitizer-mediated SDT and ferroptosis could achieve synergistic therapeutic effects against gliomas. We demonstrated that the glioma C6 cell membrane (CM) on the surface of the NPs allowed the nanosonosensitizer to accumulate selectively in tumors through homologous targeting in vitro . After efficient internalization in C6 cells, the PIOC@CM NPs could significantly increase the level of reactive oxygen species (ROS) and deplete glutathione (GSH) upon ultrasonic irradiation, resulting in the loss of glutathione peroxidase-4 (GPX4) activity, which facilitated SDT and ferroptosis to kill glioma C6 cells. Furthermore, the PIOC@CM NPs were intravenously injected after noninvasively opening the BBB via US-MBs, which enhanced the accumulation of the nanosonosensitizer in tumor tissues. Crucially, an attractive phenomenon of the significant reduction in orthotopic gliomas after the second US pulse-triggered SDT and ferroptosis was observed. Taken together, this study presents a novel combinatorial glioma therapeutic strategy based on noninvasive BBB opening with a biomimetic sonotheranostic system-mediated SDT and ferroptosis.